Pain perception in orthodontic patients: A model considering psychosocial and behavioural aspects - Campos, Lucas Arrais (2019)
Objectives: To estimate the agreement between orthodontic pain perception, evaluated with the visual analog scale (VAS), and psychosocial and behavioural aspects of pain and to estimate the impact of clinical and demographic characteristics on these aspects. Design: Cross‐sectional design using non‐probabilistic sampling. Setting and Sample Population: Orthodontic patients undergoing treatment at orthodontic clinics (n = 507 [63.3% women], mean age: 26.32 [SD = 11.70] years). Materials and Methods: Psychosocial and behavioural aspects of pain were evaluated using the Multidimensional Pain Inventory (MPI‐Orthodontic). Agreement between the pain impact level assessed according to different methods was estimated using the linear‐weighted Kappa (κp) statistic. Structural models were elaborated to estimate the impact of clinical and demographic characteristics on the psychosocial and behavioural aspects of pain. The fit of the model was evaluated, and the z test (α = 5%) was used to estimate the significance of the impact (β). Results: The agreement between VAS and MPI‐Orthodontic factors was inadequate (κp = 0.028‐0.584). The fit of the structural models was adequate. Women, younger individuals, and those who reported difficulty/pain with feeding exhibited greater perception of both the psychosocial and behavioural aspects. Individuals in lower socioeconomic strata who were not satisfied with treatment and did not seek treatment voluntarily exhibited greater perception of the psychosocial aspect of pain. Conclusions: The impact of orthodontic pain on psychosocial and behavioural aspects of patients’ lives is a relevant issue. Clinical and demographic characteristics contributed to these aspects; however, pain intensity as a sole measure may be insufficient for an adequate understanding of pain perception.